Navigating the Medical Disability Assessment and Personal Injury Claims Landscape in Malaysia - Vaikunthan Rajaratnam; K. Siladass; Sangeeta K. Singh (Public Health, 2025)
IntroductionIndividuals who have sustained permanent residual disabilities due to injuries or illnesses and relevant stakeholders engaged in the adjudication process persistently encounter obstacles in accessing equitable and just systems for assessment, support, and facilitation. These systems enable such individuals to secure appropriate compensation and lead fulfilling lives within their communities.ObjectiveThis stakeholder engagement process explores the lived experiences of individuals with disabilities and their journey through the claims processes, understanding their concerns and expectations.ResultsA total of 152 participants participated in the seminar. Thirty-nine participants with extensive experience in medical disabil-ity assessment and the claims process were purposefully surveyed, and in-depth interviews were conducted. Several themes emerged from the interview: awareness and education, the legal and judicial system and processes, expert opinion, and reports.ConclusionThe findings concluded that expert opinion and report emerged as a critical theme, with participants stressing the need for guidelines, professionalism, and accreditation for expert witnesses. Establishing a multidisciplinary regulatory body to design and develop an educational program for court experts is suggested, as is creating and maintaining a public register of court experts. Such measures will promote transparency, accountability, and quality in expert testimony and reporting